Pre-existing minor variants with NS5A L31M/V-Y93H double substitution are closely linked to virologic failure with asunaprevir plus daclatasvir treatment for genotype 1b hepatitis C virus infection. - Naoki Morishita; Ryotaro Sakamori; Tomomi Yamada; Yugo Kai; Yuki Tahata; Ayako Urabe; Ryoko Yamada; Takahiro Kodama; Hayato Hikita; Yoshinori Doi; Shinji Tamura; Hideki Hagiwara; et al. (PLoS ONE, 2020)
Background L31 and Y93 in the NS5A region of the hepatitis C virus (HCV) are the most important substitution positions associated with resistance to direct-acting antiviral (DAA) treatment. Methods We analyzed the frequency of NS5A L31M/V and Y93/H in NS5A inhibitor-naive HCV genotype 1 patients who received asunaprevir plus daclatasvir combination treatment using a conventional sequencing method and a deep sequencing method that can distinguish a single substitution at either position and a double substitution at both positions with a 0.1% detection threshold. Results The frequency of substitutions at both sites using the conventional method was very low, with 1 in 14 non-responders and 0 in 42 randomly selected responder patients. On the other hand, for the deep sequencing method, cases with double substitutions in the tandem sequence were detected in 8/14 non-responders and 1/42 responders (p<0.0001). For the conventional method, substitutions were detected at any position in 6/14 non-responders and 2/42 responders (p = 0.0019), with a clear difference between the two groups. The difference was also clear with the deep sequencing method, with 11/14 non-responders and 8/42 responders. Interestingly, for the deep sequencing method, the single substitution of L31 was found in 6/14 non-responders and 7/42 responders, whereas single substitutions of Y93 or double substitutions were found in 7/14 vs. 1/42 and 8/14 vs. 1/42 patients, respectively. Conclusions NS5A L31 and Y93 substitutions were detected in tandem by the deep sequencing methods in several genotype 1 patients, who may be more resistant to DAA treatment containing an NS5A inhibitor.